The Adventures of Oddyseus. [book 12] - McCaughearn, Geraldine (The Watts Publishing Group, 2017)
The Adventures of Oddyseus - After 10 long years at war Odysseus is coming home. But the journey is full of terrifying dangers - the man-eating cyclops, a bewitching enchantress and, worst of all, the curse of the powerful sea god Poseidon...